The Gällared Shroud: A clandestine early 19th century foetal burial - Peacock, Elizabeth E.; Tegnhed, Stina; Maltin, Emma; Turner-Walker, Gordon (Archaeological Textiles Review, 2020)
A tiny wooden box was accidentally discovered directly underneath the wooden floorboards of the 19th-century rural parish church in Gällared, Sweden during restoration building works carried out in 2015. Upon closer examination, it was revealed that the simple wooden box was a coffin containing the naturally mummified skeletal remains of a first-trimester foetus wrapped in a cotton burial shroud. This paper describes the coffin and its contents, focusing on the well-preserved burial shroud that contributed significantly to the preservation of the foetal remains. The study of the shroud provides insight into the informa􀆟 on such textile finds can contribute both to elucidating the history and evolution of the burial itself and to furthering the understanding of deliberate concealment of foetal remains within and around churches, and of infant death and grief.